Exploring the Regularity of Acupoint Selection in Acupuncture Treatment for Peripheral Facial Paralysis - Wang, Jiaxun; Liu, Zhibin (Journal of Contemporary Medical Practice, 2024)
Objective: To explore the regularity of acupoint selection in acupuncture treatment for peripheral facial paralysis. Methods: Research was conducted on the etiology and pathogenesis of facial neuritis from both traditional Chinese and Western medicine perspectives, as well as on the acupoint selection based on TCM syndrome differentiation and Western anatomical aspects. The significance of acupoint selection in different stages of peripheral facial paralysis treatment and the timing of acupuncture were summarized. Conclusion: Peripheral facial paralysis is a common clinical disease and is one of the indications suitable for acupuncture treatment. The use of a staged treatment approach, combined with the selection of acupuncture prescriptions and reinforcing and reducing techniques, has a significant effect on improving the symptoms of peripheral facial paralysis, with a predominant focus on improving facial paralysis symptoms.